Circulifer tenellus Baker and Beet mild curly top virus presence in weeds during the winter in north-central Mexico - Velásquez-Valle Rodolfo; Reveles-Torres, Luis Roberto; Amador-Ramírez Mario Domingo; Medina-Aguilar María Mercedes; Medina-García Guillermo (Revista Mexicana de Ciencias Agrícolas, 2018)
One of the most important diseases of chili pepper for drying in the north-central Mexico is called yellowing of chili. There is little information about the interaction between the vector (Circulifer tenellus Baker), the Beet mild curly top virus and weeds during the winter in this region; therefore, the objective was to identify winter weeds that serve as a refuge for the vector and host of the virus in this region. Between January and March, 2011, 26 patches of weed were sampled inAguascalientes and Zacatecas. Adult C. tenellus were captured in 69.2% of the weed sampled patches; most of the specimens were females (75.5%). Beet mild curly top was identified in only 15.4% of the sampling sites, infecting weed species such as Eruca sativa, Reseda sp., Chenopodium sp. and Solanum rostratum L.